2016
DOI: 10.1038/cgt.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA-192 as a diagnostic biomarker in human chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is known as the most common lymphoid malignancy in the Western world. MicroRNAs (miRNAs) are a class of small noncoding RNAs with pivotal roles in cellular and molecular processes related to different malignancies including CLL. Recently, some studies have shown that miR-192 plays a key role in CLL pathogenesis through increasing CDKN1A/p21 levels, suppression of Bcl-2 and enhancement of wild-type P53 and cell cycle arrest. Forty samples, including 20 patients with CLL, diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 31 publications
(41 reference statements)
1
121
0
1
Order By: Relevance
“…These molecules are small non‐coding RNA which act as negative/positive regulators in many types of biological processes such as angiogenesis (Hoseini et al, ; Mirzaei, ; Mirzaei, Khataminfar, et al, ; Mirzaei, Sahebkar, Jaafari, Goodarzi, & Mirzaei, ; Mirzaei, Yazdi, Salehi, & Mirzaei, ; Rashidi, Hoseini, Sahebkar, & Mirzaei, ; Saadatpour et al, ). It has been showed that deregulation of them via targeting a sequence cellular and molecular pathways (e.g., MAPK, Akt, VEGF, and AP‐1) lead to initiation and development of various cancers (Figure ) (Fathullahzadeh, Mirzaei, Honardoost, Sahebkar, & Salehi, ; Mohammadi, Goodarzi, Jaafari, Mirzaei, & Mirzaei, ; Reza Mirzaei et al, ; Salarinia et al, ; Simonian, Mosallayi, & Mirzaei, ). A large number studies indicated that deregulation of various miRNAs (e.g., miR‐124, miR‐155, miR‐378, miR‐17‐92 cluster, miR‐15, and miR‐16) are involved in induction/inhibition of angiogenesis in various types of cells such as cancer cells (Gallach, Calabuig‐Fariñas, Jantus‐Lewintre, & Camps, ; Landskroner‐Eiger, Moneke, & Sessa, ).…”
Section: Cdh5mentioning
confidence: 99%
“…These molecules are small non‐coding RNA which act as negative/positive regulators in many types of biological processes such as angiogenesis (Hoseini et al, ; Mirzaei, ; Mirzaei, Khataminfar, et al, ; Mirzaei, Sahebkar, Jaafari, Goodarzi, & Mirzaei, ; Mirzaei, Yazdi, Salehi, & Mirzaei, ; Rashidi, Hoseini, Sahebkar, & Mirzaei, ; Saadatpour et al, ). It has been showed that deregulation of them via targeting a sequence cellular and molecular pathways (e.g., MAPK, Akt, VEGF, and AP‐1) lead to initiation and development of various cancers (Figure ) (Fathullahzadeh, Mirzaei, Honardoost, Sahebkar, & Salehi, ; Mohammadi, Goodarzi, Jaafari, Mirzaei, & Mirzaei, ; Reza Mirzaei et al, ; Salarinia et al, ; Simonian, Mosallayi, & Mirzaei, ). A large number studies indicated that deregulation of various miRNAs (e.g., miR‐124, miR‐155, miR‐378, miR‐17‐92 cluster, miR‐15, and miR‐16) are involved in induction/inhibition of angiogenesis in various types of cells such as cancer cells (Gallach, Calabuig‐Fariñas, Jantus‐Lewintre, & Camps, ; Landskroner‐Eiger, Moneke, & Sessa, ).…”
Section: Cdh5mentioning
confidence: 99%
“…Epigenetic therapy in cancer refers to the targeting of epigenetic aberrations, which mainly depend on DNMT and histone deacetylase (HDAC) inhibitors. There is some evidence of treating some types of hematopoietic cancers, including MDS, multiple myeloma and several lymphomas . The recent results in the treatment of solid tumors with the help of epigenetic therapy are contradictory and the mechanisms are unclear .…”
Section: The Association Of Epigenetic With Cancer Treatmentmentioning
confidence: 99%
“…Among the various epigenetic players, miRNAs have appeared as new and critical players in various physiological and pathological events. MiRNAs are a type of short noncoding RNAs and act as epigenetic controllers that enable the regulation of a variety of biological processes, such as angiogenesis, growth, differentiation, metastasis, and so on . Deregulation of miRNAs is related to the initiation and progression of many diseases such as cancer, cardiovascular diseases, stroke, neurogenerative diseases, depression, and diabetes .…”
Section: Pancreatic β‐Cell Regeneration and Molecular Mechanismsmentioning
confidence: 99%